Three new species of Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from the south coast of South Africa - Sedick, Safiyya; Simon, Carol (Zootaxa, 2019)
Over the last five decades, only two new species of Syllis (Syllidae, Annelida) have been described from South Africa, suggesting a greatly underestimated richness and the expectation that many more indigenous species still remain undescribed. In this paper, we describe three new species from algal turf along a rocky shore on the south coast of South Africa. All three species are characterised by having pseudo-simple chaetae by loss of blade and enlargement of shafts together with compound heterogomph bidentate falcigers. Syllis zahri sp. nov. (up to 5 mm long) is characterised by light pink to light brown colouration on its prostomium and anterior chaetigers, dark transverse bars that fade towards the posterior region, superior anterior chaetae having short spines and posterior parapodia with distally hollow aciculae. Syllis jaylani sp. nov. (up to 7 mm long) is narrow anteriorly, relatively wider at midbody and tapers posteriorly toward the pygidium, has a pharyngeal tooth slightly back from the anterior margin, strongly bidentate chaetae with teeth perpendicular to the main shaft, thin sinuose bidentate ventral simple chaetae with a serrated edge and pseudo-simple chaetae with a serrated edge in anterior parapodia. Syllis bunaa sp. nov. (up to 9 mm long) shows a characteristic dark brown colouration on its prostomium and anterior region, is distinctly rounded dorsally, and has unidentate or minutely bidentate chaetae, up to three pseudo-simple chaetae on parapodia along the whole body and posterior ventral simple chaetae that are thick with rounded tips or sinuose with a serrated inner edge.